2020
DOI: 10.1103/physrevd.101.104046
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological signatures of torsion and how to distinguish torsion from the dark sector

Abstract: Torsion is a non-Riemannian geometrical extension of general relativity that allows including the spin of matter and the twisting of spacetime. Cosmological models with torsion have been considered in the literature to solve problems of either the very early (high redshift z) or the present-day Universe. This paper focuses on distinguishable observational signatures of torsion that could not be otherwise explained with a scalar field in pseudo-Riemannian geometry. We show that when torsion is present, the cosm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…See [587,588] for studies of the DDR. Note, the introduction of torsion is expected to lead to violations of both the curvature and DDR tests [589]. Within the context of cosmology, one way to do this is teleparallel gravity (see [590] for an up-to-date review).…”
Section: Distance Duality Relationmentioning
confidence: 99%
“…See [587,588] for studies of the DDR. Note, the introduction of torsion is expected to lead to violations of both the curvature and DDR tests [589]. Within the context of cosmology, one way to do this is teleparallel gravity (see [590] for an up-to-date review).…”
Section: Distance Duality Relationmentioning
confidence: 99%
“…That is, if dark matter is fuzzy and has intrinsic angular momentum (pointing in the direction of the dark flow or opposite to it, by 2), under our chains of assumptions), then the standard cosmological Lambda-CDM model can be augmented, with the relevant FLRW-like equations becoming (1) in [8], and the torsion produced by the corresponding nonzero value of µ = K 2 0 (in the notations of [8]) is a prediction that can (and should!) be tested experimentally [11]. In fact, as the dark flow demonstrates, there might indeed be a preferred direction in the Universe, and if the assumption of its isotropy is dropped, then the above one-parameter extension of the Lambda-CDM model is by far the simplest possible explanation of the Hubble tension even without the corroborating background provided by the general classical framework proposed in this article, and therefore it is a reasonable candidate for being given an observational test.…”
Section: Possible Cosmological Implications?mentioning
confidence: 81%
“…One sees from (143) that the simple demand of obtaining gravitational force as we did in (56) would not lead to an effective gravitational potential in geodesic motion. The choice of (144) yields a gravitational potential but with a confining large distance behaviour.…”
Section: Autoparallel Motionmentioning
confidence: 99%
“…Experimental bounds to observe space-time torsion are suggested by spin-torsion coupling [55]. Cosmological signatures of torsion are discussed recently [56]. It is shown that the angular diameter and luminosity distance become different due to torsion and it was predicted that torsion should be visible in a lower redshift which might change the interpretation of supernovae data.…”
Section: Introductionmentioning
confidence: 99%